Upstream and downstream processing of essential fatty acids from microbial biomass - Sohedein, Mohamad Nor Azzimi; Ilham, Zul; Wan-Mohtar, Wan Abd Al Qadr Imad; Taufek, Norhidayah Mohd (Frontiers in Food Science and Technology, 2023)
Microbial biomass is a promising supply of essential fatty acids (EFAs) for utilization in human and animal nutrition such as fish. EFAs, including polyunsaturated fatty acids (PUFAs), are needed for cell regulation and disease prevention. Oleaginous microorganisms from species like fungi (Cryptococcus, Cunninghamella, and Mortierella), microalgae (Chlorella zofingiensis and Crypthecodinium cohnii), and bacteria (Moritella sp. and Vibrio sp.) can accumulate lipids exceeding 20% of their biomass. Optimizing factors such as nitrogen and carbon sources, cultivation methods, and environmental conditions may improve their lipid production. Efficient lipid extraction methods through mechanical, non-mechanical or chemical methods are essential to obtain EFAs from microbial biomass. Challenges include substrates (carbon and nitrogen sources) cost and downstream processing and overcoming these challenges can provide a sustainable source of EFAs for human and animal nutrition. By advancing metabolic engineering, cultivation techniques, and extraction methods, microbial lipid production holds the potential to offer cost-effective and environmentally friendly EFAs. The utilization of microbial biomass as a source of EFAs can contribute to a healthier future by addressing the limitations of traditional sources and providing a sustainable solution for meeting the increasing demand for EFAs in human and animal diets.